Rethinking and formalizing initial teacher training on learning design for and in uncertainty - Capolla, Lorenza Maria; Giannandrea, Lorella; Gratani, Francesca; Pentucci, Maila; Rossi, Pier Giuseppe (Frontiers in Education, 2024)
The paper analyzes the impact of uncertainty on teaching and proposes a method to rethink learning design and teaching action management and to renew future teachers' training paths. Specifically, the research focuses on how learning design can help future teachers deal with the unexpected. We propose design strategies, including modularity, anticipation, hierarchy, redundancy, and deviation formalized in the "Design for the Unexpected in Education" (DUE) method, and we present the results of research conducted on initial teacher education at the University of Macerata. The data analysis of future teachers' learning designs and post-action reflections shows meaningful changes. In fact, after specific training and introducing the DUE method, future teachers can deal more confidently with the unexpected and achieve planned goals. Future teachers also refer that anxiety is reduced through prior discussion of uncertainty and available regulation strategies.